Forcing Subsets for Î³âˆ— tpw -sets in Graphs (European Journal of Pure and Applied Mathematics, 2021)
In this paper, the lower and upper bounds of the forcing total dr-power dominationnumber of any graph are determined. Total dr-power domination number of some special graphs such as complete graphs, star, fan and wheel graphs are shown. Moreover, the forcing total dr-power domination number of these graphs, together with paths and cycles, are determined.
Keywords: forcing domination; total domination; dr-power domination; path; cycle